2020
DOI: 10.1161/strokeaha.119.027843
|View full text |Cite
|
Sign up to set email alerts
|

Melbourne Mobile Stroke Unit and Reperfusion Therapy

Abstract: Background and Purpose— Mobile stroke units (MSUs) are increasingly used worldwide to provide prehospital triage and treatment. The benefits of MSUs in giving earlier thrombolysis have been well established, but the impacts of MSUs on endovascular thrombectomy (EVT) and effect on disability avoidance are largely unknown. We aimed to determine the clinical impact and disability reduction for reperfusion therapies in the first operational year of the Melbourne MSU. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 33 publications
1
70
1
Order By: Relevance
“…This result was mainly achieved by bypassing the local non-MT centres. 47 Future research will add more evidence for patients suffering from LVO and other strokes (e.g. acute ICH) and the MSU concept might facilitate the identification of novel diagnostic and therapeutic approaches that may provide benefit from ultra-early administration.…”
Section: Discussionmentioning
confidence: 99%
“…This result was mainly achieved by bypassing the local non-MT centres. 47 Future research will add more evidence for patients suffering from LVO and other strokes (e.g. acute ICH) and the MSU concept might facilitate the identification of novel diagnostic and therapeutic approaches that may provide benefit from ultra-early administration.…”
Section: Discussionmentioning
confidence: 99%
“…The Newcastle Ottawa Scale was used to assess methodologic quality across the included studies (Table 4). All but three studies 17,19,20 obtained a score of >7, suggesting overall sound methodologic quality. In terms of risk of funding bias, several studies were authored by individuals with industry funding outside of the research of interest, highlighted in Table 4.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, MSUs equipped with CTA can identify and diagnose LVO stroke patients within the MSU, allowing for accurate and appropriate triage to CSCs offering EVT. The MSUs used in the studies by Zhao et al, 20 Helwig et al, 34 and Czap et al 35 all incorporated CTA and were predominantly associated with an improvement in DTP and CTP times for MSU patients. The study by Czap et al 35 compared MSUs equipped with and without CTA for EVT patients and found a significant improvement to DTP times for the CTA equipped cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suspicion of LVO noted already during the emergency call could change the EMS’ stroke protocol. For example, sending a mobile stroke unit to the scene would give a definitive answer regarding whether the patient should be directed primarily to a comprehensive stroke centre bypassing the primary stroke centre [ 16 ]. Activation of a helicopter EMS unit to remote missions with suspected LVO could be a valuable method to decrease prehospital delays before LVO recanalization [ 17 ].…”
Section: Introductionmentioning
confidence: 99%